SOLID-LIQUID PHASE EQUILIBRIA OF U(VI) IN NACL SOLUTIONS - Daz Arocas P.; Grambow B. (My University, 1998)
Solid-liquid phase equilibria and equilibrium phase relationships of U(VI) in up to 5 m NaCl solutions were studied by analyzing the precipitation process in initially oversaturated solutions at different pH values. Comparison to corresponding behavior in NaClO4 media is made. Solid precipitates and solution concentrations of U were characterized as a function of time and pH. In NaClO4 media schoepite (UO3.2H2O) was found to be the stable phase between pH 4 and 6. By contrast, in NaCl media, sodium polyuranates formed. For a given NaCl concentration and pH, differences in the solubility concentration of about 3 orders of magnitude were observed, as attributed to metastability with respect to crystallinity and Na/U ratio of the precipitates. Average solubility constants log K°soere calculated for schoepite (log K°so = 5.37 +/- 0.25) and for Na0.33UO3.16.2H2O (log K°so = 7.13 +/- 0.15). Based on these data and together with a critical review of literature data on schoepite and polyuranates a solid solution model is developed, describing composition and phase transformation of Na-polyuranates as a function of the activity ratio Na/H in solution. Solid solution formation is rationalized within the structural context of uranyl mineral sheet structure topologies and interlayer water properties.